Effects of boron addition on the microstructure and creep properties of a Ni-Fe-based superalloy weld metal alloy. (1st February 2022) - Xie, Wencai; Wu, Dong; Lu, Shanping
Abstract: The role of boron in the creep properties and grain boundary characteristics in a new Ni-Fe-based weld metal suitable for advanced ultra-supercritical (A-USC) coal-fired power plant applications has been investigated. Ni-Fe-based filler wires without boron and boron-doped (50 ppm wt% boron) were prepared for this study. Boron-doped weld metals exhibited longer rupture lives and lower steady creep rates during the creep rupture tests at 750 °C / 380 MPa and 750 °C / 210 MPa. This study explains the improvement mechanism of boron on creep resistance from the perspective of the effect of boron on M23 C6 . Boron increased the nucleation rate of M23 C6 and participated in the formation of M23 (C, B)6 type boron-carbides. After creep deformation, boron still existed stably in the M23 (C, B)6 . The higher density of discrete M23 C6 particles due to boron addition could restrain grain boundary crack propagation and grain boundary sliding, and thereby improve the creep fracture resistance of the GH984G weld metal at 750 °C / (380/ 210 MPa).